2019
DOI: 10.1021/acsami.9b12493
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification with Gallium Coating as Nonwetting Surfaces for Gallium-Based Liquid Metal Droplet Manipulation

Abstract: We report gallium (Ga) coating as a simple approach to convert most common microfluidic substrates to nonwetting surfaces against surface-oxidized gallium-based liquid metal alloys. These alloys are readily oxidized in ambient air and adhere to almost all surfaces, which imposes significant challenges in mobilizing liquid metal droplets without leaving residue. Various flat substrates (e.g., PDMS, Si, SiO2, SU-8, glass, and parylene-C coated PDMS) were coated with thin film (75–200 nm in thickness) of gallium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…There are a number of recent reports demonstrating that the wetting behavior of liquid Ga on a surface is highly dependent on roughness rather than surface chemistry due to the presence of the Ga oxide skin (37)(38)(39), and our own experiments on particle mixing followed this behavior. Agglomerations of smaller-sized particles create a surface of higher effective roughness compared to larger-sized particles, and thus, smaller particles are nonwettable.…”
Section: Resultssupporting
confidence: 53%
“…There are a number of recent reports demonstrating that the wetting behavior of liquid Ga on a surface is highly dependent on roughness rather than surface chemistry due to the presence of the Ga oxide skin (37)(38)(39), and our own experiments on particle mixing followed this behavior. Agglomerations of smaller-sized particles create a surface of higher effective roughness compared to larger-sized particles, and thus, smaller particles are nonwettable.…”
Section: Resultssupporting
confidence: 53%
“…When the voltage above 3 Vrms and above 1 kHz was applied to the piezo-actuator, the liquid metal droplet was rapidly oscillated. An oxidized liquid metal droplet consists of pure liquid metal inside and a ~3 nm native solid gallium oxide (Ga 2 O or Ga 2 O 3 ) layer at the outmost surface [ 31 , 32 ]. The solid oxide layer on an oxidized liquid metal droplet oscillates according to the externally applied vibrational energy, which develops cracks on the solid surface oxide layer.…”
Section: Mechanism and Experiments Setupmentioning
confidence: 99%
“…One method involves removing the oxide layer using caustic agents, such as hydrochloric acid (HCl). , While this method is highly effective, allowing electrochemical actuation methods, , using such caustic agents will restrict material options, impose extra safety measures, and, due to its reactive and evaporative properties, will need to be replenished over time. Another method involves introducing foreign thin films such as Neverwet, gallium thin films, or fumed silica nanoparticles as a coating on elastomeric substrates. Neverwet is suitable for milli-scale patterns, having a reported lowest thickness limit of about 750 μm, which limits the feature size of microstructures; additionally, experience has shown that the coating tends to peel from substrates over time.…”
Section: Introductionmentioning
confidence: 99%